Efficacy of corticosteroids in prevention of acute kidney injury in neonates undergoing cardiac surgery—A randomized controlled trial. Issue 8 (17th April 2018) - Jahnukainen, T.; Keski‐Nisula, J.; Tainio, J.; Valkonen, H.; Pätilä, T.; Jalanko, H.; Suominen, P.
Abstract : Background: Heart surgery requiring cardiopulmonary bypass (CPB) causes an inflammatory response which may further induce acute kidney injury (AKI). In the present randomized controlled study we evaluated whether corticosteroids can prevent CPB related AKI in neonates undergoing heart surgery. Methods: Forty neonates were randomized to receive 2 mg/kg methylprednisolone followed by hydrocortisone infusion 0.2 mg/kg/h perioperatively with tapering doses for 5 days, or placebo administered in a similar fashion. The primary outcome was the inflammatory response (plasma concentrations of interleukins 6 and 10). The correspondence of the interleukin concentrations with AKI was analysed as secondary outcome. In addition, plasma and urine neutrophil gelatinase‐associated lipocalin (NGAL), plasma cystatin C, and urine kidney injury molecule‐1 (KIM‐1) levels were measured. Results: Six patients (15%) developed post‐operative AKI. No significant difference in the AKI occurrence between the treatment (n = 2) and the placebo (n = 4) groups could be found (risk ratio 2.00, 95% confidence interval 0.41‐9.71; P = .661) despite significant reduction in inflammatory response in the treatment group. One patient in the treatment group and two patients in the placebo group required acute peritoneal dialysis. Plasma creatinine and cystatin C or urine NGAL and KIM‐1 concentrations did not differ between the treatment and the placebo group. Conclusions: Significantly reduced inflammatory reaction induced by corticosteroid treatment in neonates undergoing cardiac surgery did not reduce the incidence of AKI defined by KDIGO classification or decrease the rise of AKI biomarkers.